Observing the behavioural effects of methylphenidate in children and adolescents with ASD-ADHD dual diagnosis: A mini review - Dimitri, Danilo; Delia, Giuliana; Arduino, Maurizio; Turco, Nazarena; Fioretto, Franco (Frontiers in Child and Adolescent Psychiatry, 2023)
Research aim: The aim of this study is to focus on the main neurophysiological aspects of attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) and the current pharmacological treatment used for the management of hyperactivity and attention deficits in children aged 6-20 years with a diagnosis of ASD. Methods:The use of methylphenidate (MPH) in clinical practice for the treatment of ASD patients presenting with comorbid ADHD was analysed with great attention paid to its efficacy in the treatment of hyperactivity and attention deficits. As this was not a meta-analysis, the transcribed data were purely descriptive. This systematic review was conducted according to the P.I.C.O. model. Conclusions: According to the existing literature, MPH has proven to be the most suitable drug for the treatment of hyperactivity and inattention in individuals diagnosed with ASD and ADHD. Two main aspects emerged from the review: (1) the need for new randomised and controlled trials to ensure a better understanding of the most effective treatments for patients with an ASD–ADHD dual diagnosis and (2) the creation and assessment of appropriate tests to analyse even more specific behavioural patterns presented in the two conditions.